The influence of complex medical treatment on the dynamics of the ankle-brachial index and extent of endothelial dysfunction in patients with multifocal atherosclerosis. - Khanyukov, О. О. (Морфологія / Morphologia / Morfologìâ, 2013)
In our investigation we studied the effect of complex medical treatment on the dynamics of the ankle-brachial index and extent of endothelial dysfunction in patients with multifocal atherosclerosis (peripheral arterial disease and chronic ischemic heart disease).Arterial insufficiency of the lower extremities and endothelial dysfunction were revealed in patients included in the study. The severity of arterial insufficiency of the lower extremities and endothelial dysfunction was more significant in patients with diabetes mellitus. The complex medical treatment provides the significant reduction of arterial insufficiency of the lower extremities and improves endothelial function in patients with multifocal atherosclerosis, including patients with diabetes mellitus.